Perbandingan Teknik 3DCRT dan IMRT pada Pasien Kanker Glioblastoma Berdasarkan Treatment Planning System - Riani, Intan Pratiwi; Papesta, Winny Rahmadani; Shafira, Hanifa; Adrial, Rico; Ilyas, Muhammad (Jurnal Fisika Unand, 2024)
Glioblastoma cancer (GBM) is a malignant brain tumour that develops aggressively and has a short life expectancy so it requires appropriate treatment for its treatment. The purpose of this study was to determine a more effective treatment technique in GBM cancer patients by comparing Three Dimension Conformal Radiation Therapy (3D-CRT) and Intensity Modulated Radiation Therapy (IMRT) irradiation techniques based on the parameters of Conformity Index (CI), Homogeneity Index (HI), maximum dose and Normal Tissue Integral Dose (NTID) of healthy tissue, as well as Dose Volume Histogram (DVH) curves obtained from the Treatment Planning System (TPS). This study used 10 GBM cancer patient data using a 6 MV photon beam and a total dose of 60 Gy. The data used are the volume of cancer when 95% of the radiation dose is given, the total volume of cancer, the radiation dose at 2%, 50%, 98%, the average dose and the volume of Organ at Risk (OAR). The results showed that the CI value for 3DCRT technique was 0.87-1.00 and IMRT technique was 0.92-0.98. HI value for 3DCRT technique is 0.02-0.07 and IMRT technique is 0.01-0.05. The percentage of the maximum dose value for the 3D-CRT technique is between 104.72% to 108.95% while the IMRT technique is between 98.40% to 108.60%. The NTID values obtained in both techniques did not exceed the established dose limits and were in accordance with the Radiation Therapy Oncology Group (RTOG) 0825 and 0615. IMRT technique is more effective than 3DCRT technique for GBM cancer patients based on CI, HI and maximum dose values.